The influence of compression molding techniques on thermal conductivity of UHMWPE/BN and UHMWPE/(BN + MWCNT) hybrid composites with segregated structure. (November 2016) - Ren, Peng-Gang; Hou, Si-Yu; Ren, Fang; Zhang, Zeng-Ping; Sun, Zhen-Feng; Xu, Ling
Abstract: Various ultra-high-molecular-weight polyethylene (UHMWPE)/boron nitride (BN) and UHMWPE/(BN + multi-wall carbon nanotube (MWCNT)) composites with segregated structure were prepared by using the compression molding process. The dispersion of fillers under different compression molding were observed by optical microscopy and scanning electron microscopy. The results showed that integrated thermal conductive networks were formed after cold-pressing sintering. However, these networks would be destroyed by middle-high pressure/high temperature treatment. Although the treatment of high pressure/high temperature can effectively improve the crystallinity and crystal size of UHMWPE, the thermal conductivity of composite dramatically decreased due to the replacement of filler-filler by filler-polymer-filler interface. The 1D-MWCNT is liable to entangle with 2D-BNs and formed MWCNT-BN networks even at high pressure/high temperature, leading to a nearly constant thermal conductivity (reached 1.794 W/m·K with the addition of 50% (BNs + MWCNT) hybrid fillers). Besides, the dispersion of the fillers have a great influence on thermal stability of the composites.